Pengaruh Kondisi Kerja, Kepuasan Kerja terhadap Kinerja Tenaga Kerja Outsourcing (Studi pada PT Bank Papua Kantor Pusat Jayapura) - Numberi, Agustinus; Setiawan, Margono (Jurnal Aplikasi Manajemen, 2013)
This research aims at examining the direct and indirect influence of working condition andworking satisfaction on outsourcing employees'performance at PT Bank Papua, Jayapura Head Office.This research is an explanatory one. The approach used in this research was quantitative research, and theresearch model was survey by using questionnaires as the instrument. The approach used in determiningselected sample for this research was based on Slovin which resulted in 110 samples. The determination ofsample unit was done using simple random sampling technique through drawing the lots of sample elements(through lottery). The analysis model applied was path analysis. The research findings proof thatworking condition has direct and significant influence on the working satisfaction. Also, the improvementof working condition has direct and significant influence on the performance of outsourcing employeesMoreover, working satisfaction influences directly and significantly the performance of outsourcing employees.Finally, working satisfaction serves as the mediator between working condition and performanceimprovement, but it is not a dominant factor in the influence of working condition on the performance ofoutsourcing employees.